2015
DOI: 10.1590/0104-0707201500003970014
|View full text |Cite
|
Sign up to set email alerts
|

Vital Signs Measurement: An Indicator of Safe Care Delivered to Elderly Patients

Abstract: The study's aim was to analyze the importance assigned by the nursing staff to the recording of vital signs of elderly inpatients, as well as perceived barriers and benefits. Data were collected through interviews held with 13 nurses and the reports were analyzed using content analysis, considering the health belief model proposed by Rosenstock. The categories that emerged from the analysis indicate barriers that interfere in the proper monitoring of vital signs, namely: workload, lack of availability and acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
0
11
0
12
Order By: Relevance
“…Care organization conducted with individuality, added to the scientific knowledge, praises professional nurses for their acknowledgment of the importance of such parameters, fundamental to care, as it foresees changes in them that allow for the identification of various diseases. In addition, controlling these parameters is essential to offer safe and quality care (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Care organization conducted with individuality, added to the scientific knowledge, praises professional nurses for their acknowledgment of the importance of such parameters, fundamental to care, as it foresees changes in them that allow for the identification of various diseases. In addition, controlling these parameters is essential to offer safe and quality care (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the first section refers to the indicators of the body's vital functions, which is important due to the fact that these data are fundamental for observing health and adequate physiology in the respiratory, cardiac, endocrine and neural areas 32 .…”
Section: The Section Evaluation Of the Basic Activities Of Dailymentioning
confidence: 99%
“…Despite the importance of BP recording for patient care, especially regarding diagnostic definition and planning of treatment and interventions, studies have shown that the conduct of nursing professionals regarding the BP documentation is still outdated and does not adequately portray the care received by the client 4-5 . In addition, the theoretical and practical knowledge about indirect BP measurement is below the expected for compliance with the technique 6-7 .…”
Section: Introductionmentioning
confidence: 99%